Involved Node, Site, Field and Residual Volume Radiotherapy for Lymphoma: A Comparison of Organ at Risk Dosimetry and Second Malignancy Risks. Issue 7 (July 2015) - Murray, L.; Sethugavalar, B.; Robertshaw, H.; Bayman, E.; Thomas, E.; Gilson, D.; Prestwich, R.J.D.
Abstract: Aims: Recent radiotherapy guidelines for lymphoma have included involved site radiotherapy (ISRT), involved node radiotherapy (INRT) and irradiation of residual volume after full-course chemotherapy. In the absence of late toxicity data, we aim to compare organ at risk (OAR) dose-metrics and calculated second malignancy risks. Materials and methods: Fifteen consecutive patients who had received mediastinal radiotherapy were included. Four radiotherapy plans were generated for each patient using a parallel pair photon technique: (i) involved field radiotherapy (IFRT), (ii) ISRT, (iii) INRT, (iv) residual post-chemotherapy volume. The radiotherapy dose was 30 Gy in 15 fractions. The OARs evaluated were: breasts, lungs, thyroid, heart, oesophagus. Relative and absolute second malignancy rates were estimated using the concept of organ equivalent dose. Significance was defined as P < 0.005. Results: Compared with ISRT, IFRT significantly increased doses to lung, thyroid, heart and oesophagus, whereas INRT and residual volume techniques significantly reduced doses to all OARs. The relative risks of second cancers were significantly higher with IFRT compared with ISRT for lung, breast and thyroid; INRT and residual volume resulted in significantly lower relative risks compared with ISRT for lung, breast and thyroid. The median excess absolute risks of second cancers were consistently lowest for the residual technique and highest for IFRT in terms of thyroid, lung and breast cancers. The risk of oesophageal cancer was similar for all four techniques. Overall, the absolute risk of second cancers was very similar for ISRT and INRT. Conclusions: Decreasing treatment volumes from IFRT to ISRT, INRT or residual volume reduces radiation exposure to OARs. Second malignancy modelling suggests that this reduction in treatment volumes will lead to a reduction in absolute excess second malignancy. Little difference was observed in second malignancy risks between ISRT and INRT, supporting the use of ISRT in the absence of a pre-chemotherapy positron emission tomography scan in the radiotherapy treatment position. Highlights: Modern lymphoma radiotherapy techniques reduce radiation exposure of normal organs. Second malignancy modelling predicts this will reduce the absolute excess second malignancy rate. The calculated second malignancy rate is similar for involved sites and involved node radiotherapy.